Оптимальне управління розподілом та перерозподілом економічних ресурсів при виборі проектів з охорони праці для машинобудівних виробництв - Левченко, Олег Григорович; Ільчук, Оксана Степанівна (НТУ "ХПІ", 2017)
У роботі обґрунтовано застосування системи моніторингу охорони праці. Визначено принципи її функціонування. Сформульовано математичну детерміновану постановку задачі параметричного програмування вибору проектів з охорони праці для машинобудівних виробництв. Розглянуто задачу вибору проектів з охорони праці за допомогою методу випадкового пошуку для трьох машинобудівних виробництв України. Визначено оптимальну сукупність проектів з охорони праці, які дають максимально можливу ефективність за результатами використання наданих економічних ресурсів.

Application of the system of monitoring of the labor protection was substantiated in the work, which makes it possible to track the production potential in each reporting period. Functions and base principles were shown. The work substantiates the need for an integrated approach to the adoption of managerial decisions on labor protection. The mathematical deterministic problem statement of parametric programming of the choice of projects for the labor protection for machine-building enterprises was formulated. The task of selecting projects on the labor protection with the method of random search for three machine-building enterprises of Ukraine is considered. The optimal set of projects on the labor protection which give the maximum possible efficiency for the results of the use of provided economic resources is determined. As a result, the set of labor protection projects remains less effective, which are not selected after a shortage of budget resources for these purposes.
Optimal management of distribution and redistribution of economic resources of the choice of projects for labor protection for machine-building enterprises
Keywords: система моніторингу; ефективність управління; метод випадкового пошуку; машинобудування; labor protection; system of monitoring; occupational safety; effectiveness of management; random search method; mechanical engineering